Analisis Dampak Faktor Fundamental Terhadap Pengembalian Saham Perusahaan Jasa Enjiniring dan Konstruksi - Bambang Santoso; Eka Anantha Sidharta; Amalia Kusuma Wardini (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
The purpose of this research is to partially analyze the effect of the company's profitability ratio (1) Current Ratio (CR), (2) Debt to Equity Ratio (DER), (3) Earning Per Share (EPS), (4) Net Profit Margin (NPM), (5) Price to Book Value (PBV), (6) Price Earnings Ratio (PER), and (7) Return On Equity (ROE) of stock returns on Engineering and Construction Services companies that have been listed on the Indonesia Stock Exchange (IDX) in the 2015Q1-2019Q2 period. This research method uses quantitative data obtained from the company's audited financial statements on the IDX during the 2015Q1-2019Q2 period. The number of samples used in this study were 10 companies (cross section). The sampling technique used is simple random sampling with criteria consisting of Engineering and Construction Services companies that have been listed on the Indonesia Stock Exchange, the company has the financial statement data for the 2015Q1-2019Q2 period (time series). Financial statement data was obtained from the official website https://idx.co.id/ during the 2015Q1-2019Q2 period. The population in this research is all of the Engineering and Construction Companies, listed on the IDX. Based on the criteria, there are 10 company samples (cross section). The regression model estimation technique using panel data is done through Common Effects Model, Fixed Effects Model, and Random Effect Model approaches.